Pendampingan Pembuatan Lahan Pertanian Produktif sebagai upaya Penanggulangan Lahan Kritis di Desa Selopamioro Imogiri, Bantul - Rahmah, Muti’ah; Febriana, Dela; Aini, Nurul; Fahrurozi, Fahrurozi; Choirina, Nadia Alfi; Himawan, Riswanda (Program Studi Ilmu Hukum Fakultas Hukum Universitas Kuningan, 2022)
The Holistic Village Development and Empowerment Program (PHP2D) by the Ministry of Education and Culture is one of the programs that accommodates student ideas and directly facilitates the needs of the community in Hamlet Nawungan I, Selopamioro Village, DIY. The critical land that composes the hamlet can be said to have promising agricultural development potential. Various government programs on land development have been launched, but until now the problem of lack of water during the dry season on the land has not been resolved. The community empowerment program proposed by the BiFloS PHP2D Team (Biology Flora Society) succeeded in obtaining a grant from the Ministry of Education and Culture in the context of efforts to deal with these critical lands. The PHP2D team is working to develop a strategy to address these challenges. Through the concept of community empowerment, the steps taken include survey activities and site selection, socialization of activities, and field schools accompanied by direct field practice. The implementation time of the activity is from August-November 2021. This activity is closed with the concept sharing with the farmers and a light interview about the sustainability of the program in the future. As a result, the farmers are very concerned about the implementation of this program in a sustainable manner.Program Holistik Pembinaan dan Pemberdayaan Desa (PHP2D) oleh Kemdikbudristek merupakan salah satu program yang mewadahi ide mahasiswa dan secara langsung memfasilitasi kebutuhan masyarakat di Dukuh Nawungan I, Desa Selopamioro, DIY. Lahan kritis yang menyusun dukuh tersebut dapat dikatakan memiliki potensi pengembangan pertanian yang menjanjikan. Berbagai program pemerintah tentang pengembangan lahan tersebut telah dicanangkan, namun sampai saat ini masalah kekurangan air saat musim kemarau dilahan tersebut masih belum teratasi. Program pemberdayaan masyarakat yang diusulkan oleh Tim PHP2D BiFloS (Biology Flora Society) berhasil mendapatkan dana hibah dari Kemdikbudristek dalam rangka upaya penanganan lahan kritis tersebut. Tim PHP2D berupaya menyusun strategi untuk menjawab tantangan tersebut. Melalui konsep pemberdayaan masyarakat, tahap-tahap yang ditempuh meliputi kegiatan survei dan seleksi lokasi, sosialisasi kegiatan, dan sekolah lapangan yang disertai dengan praktek dilahan secara langsung. Waktu pelaksanaan kegiatan terhitung dari bulan Agustus-November 2021. Kegiatan ini ditutup dengan penyamaan konsep bersama para petani dan wawancara ringan mengenai keberlanjutan program dimasa mendatang. Hasilnya, para petani sangat mengindahkan terlaksananya programini secara berkelanjutan.